Knowledge diagnostics in ergotic training system - Бабак, В. П.; Шибицький, В. П.; Ісак, А. Л. (Proceedings of National Aviation University (archive), 2021)
An information process analysis methodology from the point of view of diagnosing an operator's knowledge with the use of the etalon method approach is considered. A knowledge diagnostics algorithm is suggested which is based on a stack-list model of reasoning tree construction as well as on knowledge structure analysis.